Renal manifestations of recreational drugs: A narrative review of the literature. Issue 50 (16th December 2022) - Kannan, Lakshmi
Abstract : Drug abuse has become a major problem of the modern world where drug-induced kidney injury can be caused by both prescribed drugs for clinical conditions and illegal (illicit) drugs or drugs of abuse. Heroin, cocaine, nicotine and alcohol are the most commonly abused drugs but with the emergence of various synthetic drugs, numerous novel descriptions of their nephrotoxic effects have been described. This review summarizes the key renal manifestations of recreational drugs as reported in case reports and case. A comprehensive review of published case reports and case series in English language of renal toxicity related to recreational drugs/drugs of abuse was conducted using search engines like PubMed/Medline. Publications which reported renal injury with raised creatinine levels, clinically symptomatic patients, those with oliguria and with renal biopsies are chosen. The medical literature on recreational drugs is full of claims of renal complications including different glomerular diseases, acute kidney injury, rhabdomyolysis, interstitial nephritis, and debilitating irreversible conditions like renal infarction and end stage renal disease, even though the pathogenesis of drug- related renal manifestations are not available for all the newer agents. The outcome of this review paper will help multidisciplinary physicians to understand the renal side effects of recreational drugs, their pathophysiology, and most importantly, the clinical presentations of renal dysfunction in relation each drug. Emphasizing these adverse effects will prevent future unfavorable outcomes.